2020
DOI: 10.17478/jegys.840243
|View full text |Cite
|
Sign up to set email alerts
|

Life satisfaction for gifted adults: Its relation to gender, age, religiosity, and income

Abstract: The study's main objective is revealing the level of life satisfaction for gifted adults and its relation to gender, age, religiosity, income. The researcher used a descriptive approach with its two analytical and relational aspects. The study participants consisted of 80 (48 males and 32 females) members of the Jubilee School graduates from the first fifteen cohorts (Jubilee school is a special school for gifted and talented students in Jordan). To achieve the study goals and answer its questions, the researc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 43 publications
0
2
0
Order By: Relevance
“…Therefore, it is important that we continue to do research and study factors that have not been discovered. As addressed from previous research, moral education and religious education still have potential to contribute to the field as it combines ethics and excellence (Katanani, 2020; Nokelainen et al, 2009; Simpson, 2012; Sternberg, 2012; Tirri, 2017). In addition, as teacher education is still the key to change the identifying and serving of gifted students (Tirri, 2017), researchers should continue exploring possible factors and providing evidence to suggest possible solutions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, it is important that we continue to do research and study factors that have not been discovered. As addressed from previous research, moral education and religious education still have potential to contribute to the field as it combines ethics and excellence (Katanani, 2020; Nokelainen et al, 2009; Simpson, 2012; Sternberg, 2012; Tirri, 2017). In addition, as teacher education is still the key to change the identifying and serving of gifted students (Tirri, 2017), researchers should continue exploring possible factors and providing evidence to suggest possible solutions.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, Tirri (2010) provided how moral education provides implications for the gifted by reviewing the current empirical studies on giftedness and morality as well as providing case studies of Finnish Academic Olympians, and Sternberg (2012) addressed his thoughts and rationales regarding a role of ethics in giftedness. In terms of the empirical studies, Katanani (2020) investigated life satisfaction of 80 gifted adults with the relation to religiosity, income, age, and gender; among the results discussed, the study found no significant differences in the degree of life satisfaction due to religiosity, gender, and income, whereas age was a significant factor. By conducting a case study of mathematically gifted adolescents ( N = 20), Nokelainen et al (2009) investigated how morality and religiosity relate to intelligence; With the correlational research design, they found that moral reasoning was related to intelligence, most intelligent participants were more opposed to the lowest and highest forms of religious reasoning, the moral thinking was negatively related to the lowest and the highest stages of religious judgment.…”
Section: Literature Reviewmentioning
confidence: 99%